2015
DOI: 10.1089/chi.2015.0011
|View full text |Cite
|
Sign up to set email alerts
|

“It Hurts a Latina When They Tell Us Anything About Our Children”: Implications of Mexican-Origin Mothers' Maternal Identities, Aspirations, and Attitudes About Cultural Transmission for Childhood Obesity Prevention

Abstract: Background: This qualitative study explored values, attitudes, and beliefs held by Mexican-origin mothers of preschool-aged children to enhance understanding of cultural influences on behaviors associated with childhood obesity risk.Methods: During face-to-face interviews, 39 Mexican-origin mothers of preschool-aged children discussed their hopes for their children, their image of the perfect mother, Mexican and American foods, why they taught their children about these foods, and their opinions about televisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…For instance, children's SSB consumption may be in uenced by acculturative factors through parents' behaviors, practices, and their role shaping the home environment. [48][49][50][51] Also, we did not test for differences across Hispanic/Latino heritages due to small sample sizes, although studies among Hispanic/Latino adults have shown differences in acculturation and in SSB by heritage. 52, geographic location of study recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, children's SSB consumption may be in uenced by acculturative factors through parents' behaviors, practices, and their role shaping the home environment. [48][49][50][51] Also, we did not test for differences across Hispanic/Latino heritages due to small sample sizes, although studies among Hispanic/Latino adults have shown differences in acculturation and in SSB by heritage. 52, geographic location of study recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we are unable to make causal inferences, but rather report on the cross-sectional links (or lack thereof) and encourage future research that can elucidate the potential causal pathways (i.e., mediating factors at the family, home, and policy levels). For instance, children’s SSB consumption may be influenced by acculturative factors through parents’ behaviors, practices, and their role shaping the home environment [ 48 51 ]. Also, we did not test for differences across Hispanic/Latino heritages due to small sample sizes, although studies among Hispanic/Latino adults have shown differences in acculturation and in SSB by heritage [ 21 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, children's SSB consumption may be in uenced by acculturative factors through parents' behaviors, practices, and their role shaping the home environment. [48][49][50][51] Also, we did not test for differences across Hispanic/Latino heritages due to small sample sizes, although studies among Hispanic/Latino adults have shown differences in acculturation and in SSB by heritage. 52,53 Generalizability may be limited because some Hispanic/Latino youth may be underrepresented in relation to the geographic location of study recruitment.…”
Section: Discussionmentioning
confidence: 99%